DETERMINANTS OF ACADEMICS DISHONESTY AMONG UNDERGRADUATE ACCOUNTING STUDENTS OF ECONOMICS FACULTY OF SYIAH KUALA UNIVERSITY - Fuji, Akbar Shara; Evayani, Evayani (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This paper is written in order to discover the students' levels of tolerance towards academic dishonesty among undergraduate accounting students. Academic dishonesty acts as a predictor in which it is used to see the future attitude of students in practicing accounting later on after graduation. This research uses the ordinal regression method with variable gender form of nominal data, both relativism and idealism are the ordinal variable data, in which were observed from 2012 to 2014 in the Faculty of Economics, Syiah Kuala University. The data were processed using SPSS statistics 18. The results showed that the gender difference in both men and women did not have a significant influence to academic dishonesty itself. Furthermore, with regards in ethics; ideological idealism were found to have significant positive relationship with academic dishonesty. Therefore, the relativism that were reported within the results gave an impact towards academic dishonesty. It is anticipated that the admission of women to the growing membership of the professional accounting along with educational intervention to improve the ethical attitude of idealism can increase and help restore the reputation of the profession